2020
DOI: 10.1093/ofid/ofaa570
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency or Supplementation and the Risk of Human Herpesvirus Infections or Reactivation: A Systematic Review and Meta-analysis

Abstract: Background Vitamin D may protect against respiratory virus infections, but any association with herpesviruses is unclear. Methods We undertook a systematic review of vitamin D deficiency or supplementation and the risk of 8 human herpesviruses. Six databases and 4 gray literature databases were searched for relevant cohort studies, case–control studies, and clinical trials. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…10. 3389/fmicb.2022.1102130 Frontiers in Microbiology 10 frontiersin.org vitamin D deficiency related low sun exposure in winter, especially in people >70 years old, as previously reported (Lin et al, 2019(Lin et al, , 2020Cristian Ilie and Stefanescu, 2020). Accordingly, significant correlations between pathogen, gender and age differentially observed in Nimes and Marseille may simply reflect differences in the population structure in these two different cities.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…10. 3389/fmicb.2022.1102130 Frontiers in Microbiology 10 frontiersin.org vitamin D deficiency related low sun exposure in winter, especially in people >70 years old, as previously reported (Lin et al, 2019(Lin et al, , 2020Cristian Ilie and Stefanescu, 2020). Accordingly, significant correlations between pathogen, gender and age differentially observed in Nimes and Marseille may simply reflect differences in the population structure in these two different cities.…”
Section: Discussionsupporting
confidence: 69%
“…Accordingly, in 2018 ( Broberg et al, 2018 ), the unusual persistence of mixed Enterovirus and Human parechovirus outbreaks infecting new-borns and children until the autumn correlated with a notable 2°C increase in autumn temperatures in October/November 2018 compared to seasonal norms ( Cabrerizo et al, 2015 ). Most intriguing was the observation that DNA viruses also adopted an outbreak pattern, with HSV-1 CAM being observed in elderly male patients in January–March, probably due to the HSV-1 reactivation ( Dudgeon, 1969 ; Taylor et al, 2002 ), which is potentially prompted by vitamin D deficiency related to low sun exposure in winter, especially in people >70 years old, as previously reported ( Lin et al, 2019 , 2020 ; Cristian Ilie and Stefanescu, 2020 ). Accordingly, significant correlations between pathogen, gender and age differentially observed in Nimes and Marseille may simply reflect differences in the population structure in these two different cities.…”
Section: Discussionmentioning
confidence: 53%
“…A systematic review and meta-analysis published in 2021, combining 37 clinical trials of vitamin D supplementation, showed that taking vitamin D slightly decreased the risk of respiratory infections (odds ratio = 0.92, 95% CI = 0.86-0.99) (11). Our previous systematic review and meta-analysis found inconclusive evidence for any association between vitamin D and herpesviruses in studies conducted primarily among immunosuppressed individuals (12). One case-control study among people with CKD showed that vitamin D supplementation may decrease the odds of herpes zoster (13).…”
Section: Introductionmentioning
confidence: 87%
“… 11 The authors’ previous systematic review and meta-analysis found inconclusive evidence for any association between vitamin D and herpes viruses in studies conducted primarily among individuals who were immunosuppressed. 12 One case–control study among people with CKD showed that vitamin D supplementation may decrease the odds of HZ. 13 …”
Section: Introductionmentioning
confidence: 99%